Exploring Wattpad Application Usage Patterns Among Students in Reading Narrative Texts at SMPN 28 Bekasi - Fiiryal Azzahra; Franscy Franscy; Subadar Subadar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Reading is an interactive process where readers construct meaning from texts, relying on various skills, including comprehension. It is fundamental for learning and daily life, and its importance is underscored by the rise of information and communication technology (ICT), which facilitates access to information through tools like the internet. Online platforms, such as Wattpad, have emerged as popular resources for improving literacy among students, particularly in narrative texts. At SMPN 28 Bekasi, English is a compulsory subject, yet students face challenges in reading comprehension, especially in understanding narrative texts. Despite the implementation of the Kurikulum Merdeka, which focuses on project-based learning, many students struggle to meet reading standards. This research aims to investigate the impact of the Wattpad application on students' reading comprehension of narrative texts, given their difficulties and lack of engagement with traditional reading materials. The survey revealed mixed preferences among students, with strong leanings towards novels (45%), fiction (56%), and romance (44%). Short stories are less popular but still attract the interest of some readers. The majority of students (46.7%) use Wattpad daily, spending mostly 30-60 minutes per session. Many read 2-4 texts per month and often follow specific authors. About 60% of students use bookmarks regularly, while 66.7% prefer texts recommended by Wattpad. The note-taking feature shows mixed use, indicating varying levels of engagement. Reviews and ratings are very important to 83.3% of students when selecting texts. Students generally felt confident in following the storyline (83.3% often or always), analyzing characters (83.3%), and identifying the main conflict (83.3%). Most students apply information from texts in real life, frequently reread for clarity, and often create summaries. Overall, these findings demonstrate high engagement and understanding among Wattpad students, demonstrating their diverse reading habits and interactive use of the platform.